Analysis of risk factors for perioperative hyperamylasemia in kidney transplant recipients - Yang Zhang; Liubing Xia; You Luo; Jinhua Zhang; Zoufu Tang; Xiaorong Chen; Ning Na (Renal Failure)
Background Perioperative hyperamylasemia has been observed in several kidney transplant recipients (KTRs) at our center. However, there are currently no published reports on this observation. This study aimed to identify the risk factors associated with perioperative hyperamylasemia in KTRs.Methods The data from 540 deceased-donor kidney recipients in our hospital from January 2020 to December 2023 were retrospectively analyzed. Variables such as gender, past medical history, relevant laboratory tests, and trough concentration of calcineurin inhibitors (CNIs) at the time of serum amylase maximum were collected for all patients. Univariate and multivariate logistic regression analyses were used to determine the risk factors associated with perioperative hyperamylasemia.Results Among all KTRs, 153 patients (28.3%) developed perioperative hyperamylasemia. Multivariate logistic regression analysis indicated that preoperative serum phosphate (odds ratio [OR] = 1.62, 95% confidence interval [CI]: 1.160 − 2.266, p = 0.005), preoperative serum amylase (OR = 1.01, 95% CI: 1.006 − 1.015, p < 0.001), and high perioperative CNIs trough concentration (OR = 2.335, 95% CI: 1.560 − 3.494, p < 0.001) were risk factors associated with perioperative hyperamylasemia. In addition, we used all three as a hybrid model to predict perioperative hyperamylasemia, which demonstrated good predictive value (area under the ROC curve [AUC] = 0.687, 95% CI: 0.64–0.734).Conclusion Elevated preoperative serum phosphate levels, preoperative serum amylase levels, and high perioperative CNIs trough concentrations are risk factors for perioperative hyperamylasemia. This study may provide valuable insights for clinicians to identify the causes of perioperative hyperamylasemia and formulate prevention and treatment strategies.